2019
DOI: 10.22159/ijcpr.2019v11i5.35704
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Nigella Sativa Oil on Chemoradiation-Induced Oral Mucositis in Patients With Head and Neck Cancers

Abstract: Objective: Oral mucositis (OM) is a common treatment-induced toxicity in patients undergoing radiation or chemoradiation for head and neck cancers (HNC). The study aims to evaluate the anti-inflammatory effect of Nigella sativa (NS) oil in radiation-or chemoradiation-induced OM in HNC patients. Methods:From Forty HNC patients were randomized to two groups, each of 20 patients. The first group was treated with NS oil mouthwash five times daily, while the second group was treated with the Magic mouthwash and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In this trial, N. sativa oil mouthwash and Magic mouthwash were given to the research participants. Results of this trial indicated a significant reduction in the severity of oral mucositis after 3-4 weeks of radiotherapy 20 . Another clinical trial was conducted to treat oral mucositis in patients with acute myeloid leukemia (n=54) using N. sativa oil mouth rinse and magic mouthwash respectively.…”
Section: Table 1: Evaluation Of Pain/burning Sensation and Interincis...mentioning
confidence: 86%
“…In this trial, N. sativa oil mouthwash and Magic mouthwash were given to the research participants. Results of this trial indicated a significant reduction in the severity of oral mucositis after 3-4 weeks of radiotherapy 20 . Another clinical trial was conducted to treat oral mucositis in patients with acute myeloid leukemia (n=54) using N. sativa oil mouth rinse and magic mouthwash respectively.…”
Section: Table 1: Evaluation Of Pain/burning Sensation and Interincis...mentioning
confidence: 86%
“…Patients in Group A were asked to use NS oil mouthwash 5 times a day whereas participants in Group B were given Magic mouthwash and were instructed to use it in a similar manner. The results of this trial showed decrease in the severity of oral mucositis, which was assessed using the radiation therapy oncology group (RTOG) guidelines in chemotherapy or chemo-radiotherapy, treated HNSCC patients after using N. sativa oil mouthwash 28 .…”
Section: Nigella Sativa In Preventing Oral Mucositis In Head and Neck Squamous Cell Carcinoma (Hnscc)mentioning
confidence: 99%